Evaluation of the impact of the implementation of accountability accounting and logistics management on company performance (case study at PT. Javanusa Multi Cargo Semarang City) - Sumaroh, Sumaroh; Lutfi, Lisda Samara; Suhantoro, Suhantoro (Jurnal Ekonomi, 2024)
Research with the problem "Evaluation of the Impact of the Application of Responsibility Accounting and Logistics Management on Company Performance" Case Study at PT Javanusa Multi Cargo Semarang City aims to identify, study, examine and evaluate the impact of the application of responsibility accounting and logistics management on company performance" at the Logistics Company PT Javanusa Multi Cargo Semarang City. The population of this study is The population used in this study were employees at PT Javanusa Multi Cargo Semarang City, totaling around 50 people. The employees are devoted to those who directly do the work in the office to be more aware of the strategic aspects. with sampling techniques using purposive sampling method by taking research samples based on certain criteria.... Purposive sampling is used because the information to be taken comes from sources that are deliberately selected based on certain criteria that have been set by researchers with samples used in this study are as follows: a.Employees who carry out the responsibility function at PT Javanusa Multi Cargo Semarang City. b.Have a minimum work period of one year in the accountability function. The data used is primary data with data analysis methods using multiple linear regression analysis.The results showed that the Evaluation of the Impact of the Application of Responsibility Accounting and Logistics Management had a positive and significant effect on the Company's Performance at PT Javanusa Multi Cargo Semarang City.